Declining TPQ Enrollment from a Community Social Support Perspective in Paloma Regency Makamhaji - Khairunnisa, Salsabila; Maksum, Muh. Nur Rochim (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2026)
This study aims to analyze the form of community support for the sustainability of the Al-Qur'an Education Park (TPQ), find out the causes of the decline in the number of students, and analyze the relationship between community support and children's participation in TPQ activities in the Paloma Regency Makamhaji Housing area. The qualitative method was applied in this study by conducting interviews with parents or guardians of students as the main informant. The collected data were analyzed descriptively to understand the phenomenon of children's participation in non-formal religious education. The results of the study show that community support for TPQ is in the good category, but tends to be passive and not optimal in terms of active involvement. The main cause of the decline in the number of TPQ students comes from the internal condition of children, especially fatigue due to many activities in formal schools and additional activities outside of school. Community support plays a role as a contextual factor that influences children's motivation and views on the value of the importance of TPQ, but not as a major determinant of participation. In addition, this study also found that TPQ's internal strategies, such as innovation in learning, improving communication with parents, and involving local youth, are important steps in maintaining the sustainability of students amid declining community support. Therefore, the sustainability of TPQ is highly dependent on the ability of the institution to adapt to the needs of students and the social dynamics around it. The findings of this research are expected to be a consideration for TPQ managers, the community, and related parties in formulating policies and strategies for the management of non-formal religious education that are more sustainable and responsive to social change.